Ultrasonication pretreatment assisted rapid co-assembly of cellulose nanocrystal and metal ion for multifunctional application. (1st February 2022) - Qin, Jinli; Li, Na; Jiang, Min; Zong, Lu; Yang, Hongsheng; Yuan, Yuan; Zhang, Jianming
Abstract: Co-assembly of metal ion and cellulose nanocrystals (CNC) is a promising strategy to fabricate novel iridescent CNC materials with advanced applications. By combining ultrasonication pretreatment and vacuum-assisted self-assembly (VASA) technique, a facile and rapid strategy is proposed to prepare the Mn 2+ -doped carboxylated CNC (C-CNC) iridescent films with multifunctional application. The ultrasonication pretreatment temporarily disassembles the aggregates of C-CNC nanorods caused by the electrostatic interaction between negative charged C-CNC and Mn 2+ . The subsequent VASA process accelerates the self-assembly of chiral liquid crystals prior to the re-agglomeration of C-CNC by the bridge effect of Mn 2+ . Furthermore, the as-prepared Mn 2+ /CNC film exhibits a rapid and visible color change in ammonia atmosphere along with the formation of MnO2 . The reversible change can be realized by the stimulation of reducing agent. The derived MnO2 /C-CNC composite film displays efficient removal of methylene blue dye in aqueous solution by both of adsorption and degradation procedure. Graphical abstract: Unlabelled Image